SEEKING SELF-WORTH THROUGH COMMODITY NARCISSISM & COMMODITY NIHILISM IN THE LIGHT OF SECULAR AND TAWHIDI PARADIGMS - Aydin, Necati (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
With the depiction of Western lifestyles in various media outlet at the global level, the desire for conspicuous consumption has reached an all time high. Why do people engage in conspicuous consumption? Generally speaking, we could put these motivations under two categories: intrinsic and extrinsic. In this paper, we will examine one of the intrinsic factors behind conspicuous consumption: self-worth. Even though there are some studies exploring the relationship between self-esteem and consumption, this is the first study exploring the relationship between self-worth and consumption. The paper is organized as follows: First, it provides a brief review of how humans lost value since the Enlightenment through the adoption of a secular paradigm in both the modern and post- modern eras. Second, it examines the engagement of conspicuous consumption due to self-worth depletion through commodity fetishism, commodity narcissism, and commodity nihilism. Third, it outlines the Tawhidi paradigm in terms of its ontological, epistemological, anthropological, and teleological worldviews. Fourth, it explores self-worth from the perspective of Tawhidi paradigm. Fifth, it compares secular and the Tawhidi paradigms in terms of their contribution to conspicuous consumption because of self-worth depletion.